Economic burden of asthma in Abu Dhabi: a retrospective study - Alzaabi A; Alseiari M; Mahboub B (Dove Medical Press, 2014)
Ashraf Alzaabi,1 Mohammed Alseiari,2 Bassam Mahboub3 1Respiratory Medicine Division, Zayed Military Hospital, Abu Dhabi, United Arab Emirates; 2General Secretariat of Executive Council, Abu Dhabi, United Arab Emirates; 3University of Sharjah, Rashid Hospital, Sharjah, United Arab Emirates Abstract: This study evaluates the direct costs of treating asthma in Abu Dhabi in the United Arab Emirates. Data was compiled for 2011 from health insurance claims covering all medical interventions or treatments coded as asthma. Costs were calculated from a health care perspective. The total direct cost of treating 139,092 asthma patients was estimated to be United Arab Emirates Dirhams (AED) 105 million (US$29 million), corresponding to around AED 750 per patient per annum. The total cost is principally generated by outpatient visits (>AED 85 million; 81% of the total cost). Ten point four percent of patients had made an emergency room visit. The cost per visit seems to be higher during hospital admissions (AED 7,123) compared to outpatient visits and emergency room visits. The direct cost of asthma medications was around AED 33 million (31% of the total cost). The economic burden of asthma in Abu Dhabi is high and the number of emergency visits suggests that the disease is not optimally controlled. Keywords: asthma, cost, Abu Dhabi, UAE, Middle East